Huoxin Pill inhibits isoproterenol-induced transdifferentiation and collagen synthesis in cardiac fibroblasts through the TGF-β/Smads pathway. (15th July 2021) - Peng, Meizhong; Yang, Meiling; Lu, Yan; Lin, Shan; Gao, Huajian; Xie, Lingling; Huang, Bin; Chen, Daxin; Shen, Aling; Shen, Zhiqing; Peng, Jun; Chu, Jianfeng
Abstract: Ethnopharmacological relevance: The abnormal proliferation and differentiation of cardiac fibroblasts (CFs) are universally regarded as the key process for the progressive development of cardiac fibrosis following various cardiovascular diseases. Huoxin Pill (Concentrated pill, HXP) is a Chinese herbal formula for treating coronary heart disease. However, the cellular and molecular mechanisms of HXP in the treatment of myocardial fibrosis are still unclear. Aim of the study: To investigate the effects of HXP on CFs transdifferentiation and collagen synthesis under isoproterenol (ISO) conditions, as well as the potential mechanism of action. Materials and methods: In vivo, we established a rat model of cardiac fibrosis induced by ISO, and administered with low or high dose of HXP (10 mg/kg/day or 30 mg/kg/day). The level of α-SMA was detected by immunohistochemistry examination, and combined with RNA-sequencing analysis to determine the protective effect of HXP on myocardial fibrosis rats. In vitro, by culturing primary rat CFs, we examined the effects of HXP on the proliferation and transdifferentiation of CFs using CCK8, scratch wound healing and immunofluorescence assays. Western blot was used to determine protein expression. Results: The findings revealed that HXP protects against ISO-induced cardiac fibrosis and CFs transdifferentiation in rats. RNA-sequencing and pathway analyses demonstrated 238 or 295 differentially expressed genes (DEGs) and multiple enriched signal pathways, including transforming growth factor-beta (TGF-β) receptor signaling activates Smads, downregulation of TGF-β receptor signaling, signaling by TGF-β receptor complex, and collagen formation under treatment with low or high-dose of HXP. Moreover, HXP also markedly inhibited ISO-induced primary rat CFs proliferation, transdifferentiation, collagen synthesis and the upregulation of TGF-β1 and phosphorylated Smad2/3 protein expression. Conclusion: HXP suppresses ISO-induced CFs transdifferentiation and collagen synthesis, and it may exert these effects in part by inhibiting the activation of the TGF-β/Smads pathway. This may be a new therapeutic tool for cardiac fibrosis. Graphical abstract: Image 1